Controllable synthesis of multi-shelled SiO2@C@NiCo2O4 yolk–shell composites for enhancing microwave absorbing properties. (2nd November 2021) - Wang, Shanshan; Zhu, Huanhuan; Jiao, Qingze; Jiao, Xiaoguang; Feng, Caihong; Li, Hansheng; Shi, Daxin; Wu, Qin; Zhao, Yun
Abstract : NiCo2 O4 grows uniformly on the surface of a yolk–shell SiO2 @C sphere and exhibits strong microwave absorption. Abstract : With the increasingly serious pollution of electromagnetic radiation, the task of developing light and strong wave-absorbing materials is becoming more and more urgent. In this study, a novel SiO2 @C@NiCo2 O4 -1 : 3 composite with a multi-shelled yolk–shell structure was designed and fabricated. NiCo2 O4 with a lamellar structure grows uniformly on the surface of the C sphere, and there is an obvious cavity between the C shell and the SiO2 sphere. This unique structure not only improves the impedance matching characteristics of the composite but also produces rich interfaces and increases the dielectric loss. Compared with pure SiO2 @C and NiCo2 O4, SiO2 @C@NiCo2 O4 shows stronger microwave absorbing properties, and SiO2 @C@NiCo2 O4 -1 : 3 exhibits the strongest absorption of microwaves only with a loading of 15 wt%. Its minimum reflection loss (RLmin ) is −46.96 dB, and the effective absorption band (EAB, RL <−10 dB) is 3.76 GHz. These results reveal that the multi-shelled SiO2 @C@NiCo2 O4 -1 : 3 composites are promising microwave absorbers.